Examining Affirmative Action in Perspective of Law and Globalization In Indonesia - Yudhanti, Ristina (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Globalization is a global process which is unavoidable by everyone whoKeywords: Globalization, Affirmative Policy, Gender Equality.wants to interact with the international world because those who avoid it willbe isolated from the advance and even from the internationalassociation. Globalization as a must gives big impacts to the human lifeincluding the political, economical, social-culture, and legal impacts. Law is neversterile from the aspects outside law, because law is always dynamic and willfollow the societyâs development. When the Globalization era emerges, lawalso follows the rhythm of the latest era. The interesting thing is that law andglobalization is related to the emergence of the movement of awareness on thegender equality in all over the world. The movement which was pioneered bythe feminist movement in all over the world wanted Human Rights equal WomanRights. The existence of CEDAW Convention which was later ratified by theIndonesian government.Gender equality is a hard-struggle of women in reaching the globalcommitment on the respect of Human Rights. Gender inequality is veryapprehensive especially in the developing countries in the world.Inequalities in politics, law, economy, and social cause the low level ofparticipation of women community and relatively have not raised theirfunction as the balanced competitor compared to the men community and thesocial construction that has a significant influence on the gender inequality.Gender equality is a global movement as a reflection on the inequalityagainst women. There is a stereotype or a negative labelling that viewswomen are lower (subordinate) than men. Even, many myths and beliefs thatcause women are often viewed from merely sex aspect, not from their ability,opportunity, and human aspects universally, that is as human being who hasintelligence, logic, feeling, and equality before the law.In the political field, the determination of representative target (quota) is as muchas 30% for women in the candidacy of Members of The House ofRepresentative in central and regional that aims at knowing the correlationbetween the woman representation in the parliament and the process of publicstrategic decision making. It means to see whether the affirmative policyfunctions effectively and is not only formality. Therefore, it caused an obstaclein struggling the strategic issues in the parliament, although the participation ofevery member of the house of representative is open democratically in everystrategic decision making.